Clinical Profile of Psoriasis Vulgaris at Soetomo General Hospital, Surabaya - Nadya Kelfinta Hanani; Evy Ervianti; Alphania Rahniayu (Health Notions, 2020)
Psoriasis vulgaris is a progressive chronic inflammatory skin disease. The prevalence of psoriasis vulgaris in the world, and in Indonesia itself. Psoriasis vulgaris brings a negative effect on patient’s physical, emotional and psychosocial aspect. This study as aimed to evaluate the clinical profile of psoriasis vulgaris in the Soetomo General Hospital Surabaya, in the period of 2016-2018. This was a retrospective descriptive study using the medical record data. The results showed that 201 patients with psoriasis vulgaris. The majority of psoriasis vulgaris cases were males (51.24%), aged 46-55 years old patients (26.87%), occupations as private employees (45.27%), triggering factor was hypertension (26.86%), common complaint was red patches (66.17%), common clinical presentation was erythematous macules (90.54%), the occurrence of chronic residif was (61.69%), typically found in the whole body (57.21%), degree of severity was ‘severe’ (21.89%), duration of disease was 3 months (45.27%), the percentage of sharing a similar disease with family was (0.99%), diagnosed by Histopathology examination was (38.31%), the most common employed systemic therapy and topical was cetirizine (25.87%) and desoxymethasone cream (27.36%). Psoriasis vulgaris diagnosis is done by carrying out an anamnesis and clinical symptoms, and the results were then compared to the results of histopathological examination. Keywords: psoriasis vulgaris; retrospective; profile; Surabaya